Simulation of the high power ultrashot optical pulse propagation in single mode optical fibers - Zhou, Chiying (Nanyang Technological University, 2022)
For high power pulses, some higher order nonlinearities are considered, including Raman scattering and self-steepening effects. For the pulses with multidimensional components, some Inter-component effects would also happen, including four-wave mixing and cross-phase modulation. In this thesis, firstly, the propagation equations of pulses in optical fibers are derived. Then the causes and effects of dispersion and various nonlinear effects are described, and different types of optical solitons and their generation devices are introduced. Next, for the linear and nonlinear effects mentioned in the thesis, these different high-power ultrashort optical pulses propagation in single-mode fibers are numerically simulated and discussed.